(untitled) (Revista Contexto & Educação, 2019)
The aim of the present study was analyzed the Brazilian scientific production on biology teaching in Youth and Adult Education (YAE). It is a State of the Art that characterizes this production as the distribution (space and time) and discusses the aspects that aroused the intellectual interest of researchers to produce knowledge about the teaching of biology in the YAE. The corpus of the analysis consisted of articles (28), dissertations (54) and theses (02). The selection of articles considered the field of investigation, the impact factor of the periodical, period and the search descriptors. The selection of dissertations and theses involved the identification of postgraduate programs in the field of education and teaching, period and descriptors. All study was based on the categories of fleckian epistemology. The results indicate an asymmetry in the distribution of the research in the Brazilian regions. The activity of teachers of basic education is the most important aspect involved in scientific production, since the practice of teaching biology in the YAE modality is imbued with elements of resistance and constitute the passive connections mediated by the active connections of the Collective of Researchers in Science Education (CRSE).